Collaborating for policy impact: Academic-practitioner collaboration in industrial relations research. (November 2022) - McGrath-Champ, Susan; Gavin, Mihajla; Stacey, Meghan; Wilson, Rachel
Knowledge co-production between academics and practitioners is increasingly a focus for university workplace contexts. While there is emerging interest in how social science academics can engage with industry to generate impact, little attention has been paid to how one form of practitioner organisation, trade unions, engages with academics to influence policy and member outcomes. In this article, we examine a case of research collaboration with an education trade union based in New South Wales, Australia, to explore the process of knowledge co-production with this partnership and its impact on education policy. In examining this decade-long partnership, we contribute to the literature on union strategy by depicting collaboration with researchers as a unique strategy for influencing policy outcomes (in this case, addressing teacher workload), while also contributing to emerging scholarship on knowledge co-production as a means to generate impact beyond the academy. As such, this article contributes a rare example of 'cross-over' between the worlds of academia and industry, which may inform future engagement and impact processes.